Prevalence and Correlation of Knowledge Levels with the Physical Activity of Hypertension Patients - Heri Ariyanto; Andika Abdul Malik; Wina Widianti; Windi Oktavia (Inspirasi Foundation, 2020)
Introduction: As many as 1 billion people in the world or about 1 in 4 adults suffer from hypertension. Many people with hypertension still ignore their disease, even though if left untreated it will lead to further complications. This is because knowledge about hypertension affects the quality of life for people with hypertension. Method: This study aims to determine the relationship between the level of knowledge and the physical activity of people with hypertension. This study used a quantitative analytic study with a cross sectional approach. The sampling technique used proportional random sampling. The study population was 100 people, and a total sample of 50 people. The research instrument used an accurate knowledge questionnaire of 20 items to see the level of knowledge and a physical activity questionnaire on the SF-12 to see the quality of life. Result: The results showed that the respondents had more knowledge than the average yaiu as many as 32 people (64%). While the physical activity of respondents in the good category was 25 people (50%). Conclusion: Based on the results of the analysis, the conclusion is that there is a significant relationship between knowledge and physical activity in patients with hypertension as evidenced by the value of ρ value =0.002 and the value of chi square (X2) = 9.810.